2021
DOI: 10.1039/d1nr01281a
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of cesium acetate in the sequential deposition method for perovskite solar cells

Abstract: The cesium cation (Cs+) widely used as dopant for highly efficient and stable formamidinium lead tri-halide perovskite (FAPbX3, X=I, Br, Cl) solar cells. Herein, we introduce a small amount of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…The calculated hole mobility for control Cs 2 AgBiBr 6 film and 1.0MABr film are 8.7 × 10 −5 and 1.3 × 10 −4 cm 2 V −1 S −1 , respectively. The calculated trap density is quite comparable to that of lead‐halide perovskites, [ 28 ] suggesting the potential of this Cs 2 AgBiBr 6 double perovskites in optoelectronic applications. An increased carrier mobility was also observed after MABr optimization.…”
Section: Resultsmentioning
confidence: 69%
“…The calculated hole mobility for control Cs 2 AgBiBr 6 film and 1.0MABr film are 8.7 × 10 −5 and 1.3 × 10 −4 cm 2 V −1 S −1 , respectively. The calculated trap density is quite comparable to that of lead‐halide perovskites, [ 28 ] suggesting the potential of this Cs 2 AgBiBr 6 double perovskites in optoelectronic applications. An increased carrier mobility was also observed after MABr optimization.…”
Section: Resultsmentioning
confidence: 69%
“…[26][27][28] Tumen-Ulzii et al found that unreacted PbI 2 photodecomposes into lead and iodine under illumination, which greatly accelerates the degradation of PSCs. [29] Therefore, the content of PbI 2 on the surface of perovskite film should be carefully controlled. Many efforts have been made to reduce and passivate residual PbI 2 by adding additives to the bulk phase of perovskite, rather than through surface passivation strategy.…”
Section: Introductionmentioning
confidence: 99%
“…[26] Kim et al found that a small amount of cesium acetate (CsAc) would stabilize the phase structure, Ac À participated in the interaction between PbI 2 -DMSO inter-mediate phases and reduced the trap density. [29] Chen et al found that acetate ions could recrystallize perovskite layer in the vertical direction to the substrate by the process of acetate ions moving up after spin coating FAI, then passivate the iodine vacancy defects and form coordination bonds with lead ions on the surface. [30] However, reducing residual PbI 2 and promoting the conversion of perovskite in the sequential deposition method still represents an important challenge, and requires more effective solution.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations